Mitochondrial DNA Content Contributes to Climate Adaptation Using Chinese Populations as a Model - Cheng, Yao-Ting; Liu, Jia; Yang, Li-Qin; Sun, Chang; Kong, Qing-Peng (PLOS ONE, 2013)
Maintaining a balance between ATP synthesis and heat generation is crucial for adapting to changes in climate. Variation in the mitochondrial DNA (mtDNA), which encodes 13 subunits of the respiratory chain complexes, may contribute to climate adaptation by regulating thermogenesis and the use of bioenergy. However, studies looking for a relationship between mtDNA haplogroups and climate have obtained mixed results, leaving unresolved the role of mtDNA in climate adaptation. Since mtDNA content can regulate human bioenergy processes and is known to influence many physiological traits and diseases, it is possible that mtDNA content contributes to climate adaptation in human populations. Here, we analyze the distribution of mtDNA content among 27 Chinese ethnic populations residing across China and find a significant association between mtDNA content and climate, with northern populations having significantly higher mtDNA content than southern populations. Functional studies have shown that high mtDNA content correlates with an increase in the expression of energy metabolism enzymes, which may accelerate thermogenesis. This suggests that the significantly higher mtDNA content observed in northern populations may confer a selective advantage in adapting to colder northern climates